Lobbying do terceiro setor na democracia: tratamento constitucional - Benine, Renato Jaqueta (2011)
Lobbying is an expression constantly associated with the defense of private and specific economic interests of a group and with the adoption of shady practices, influence peddling, corruption and exchange of favors. However, this practice which should not be understood from its pathology but from its physiology has become increasingly common, being used not only as a defense mechanism of an economic group, but also as an instrument to promote overall interests in a society. In this scenario, we also have organizations of the emerging Third Sector figuring as actors adopting lobbying strategies. In Brazil, the regulation of lobbying practice is still pending. However, its physiology has deserved a legal and constitutional treatment in the 1988 Federal Constitution. Its protection is observed with the recognition of citizenship and political pluralism as the foundation of the Democratic State ruled by the Law, as well as from the participatory democratic dimension, expressed by the 88 Constitution. The fundamental status of lobbying in the Third Sector also derives from the recognition of fundamental rights and guarantees, including: (a) freedom of assembly; (b) freedom of association; (c) the right to be informed; (d) the right to information ; (e) the right to freedom of opinion and expression of thought; (f) the freedom of intellectual, scientific expression and others; and (g) the right of petition. As to the limits of this practice, they are perceived in its own constitutional provisions to guarantee such protection. Concerning freedom of assembly and freedom of association, the lobbying carried out by Third Sector organizations is thought to be developed for lawful purposes. As to citizenship understood as a duty of solidarity with other members of society it is understood that the Third Sector, in an act of lobbying, must be aware of social concerns like those expressed among the fundamental objectives of our federal republic. Another limit to the Third Sector lobbying is the political equality to which all are endowed with equal rights and freedom in the development of a political action. Thus, no action developed by lobbying organizations of the Third Sector could be generated so as to eliminate or prevent the participation of other interest groups, opposed or not, because dissension is a vital component of our pluralist democracy.